Cold brewing of rooibos tea affects its sensory profile and physicochemical properties compared to regular hot, and boiled brewing. (October 2020) - Muller, Magdalena; De Beer, Dalene; Truzzi, Cristina; Annibaldi, Anna; Carloni, Patricia; Girolametti, Federico; Damiani, Elisabetta; Joubert, Elizabeth
Abstract: Cold brewing of rooibos tea has gained popularity, in particular in Japan, one of its major markets, due to the convenience of preparation. The sensory profile of traditional ('fermented') rooibos, prepared by regular brewing (5 min infused in freshly-boiled water) and served hot, is well described. However, no sensory profiling of cold-brewed rooibos tea, rooibos tea served at ambient temperature, or green rooibos tea has been performed to date. In this study, the sensory profile of both fermented and green rooibos prepared by cold brewing (8 h at ≤5 °C), regular hot brewing and boiling (5 min), and consumed at ambient temperature (21 °C), were investigated. 'Rooibos woody' and 'fynbos-floral' aroma notes of fermented rooibos were unaffected by brewing procedure, but its cold brew was sweeter and less astringent than the other brews. The sensory profile of green rooibos, dominated by a 'hay/dried grass' aroma, bitter taste and astringency, was affected to a greater extent by brewing procedure, but mostly, cold and regular brews had similar aroma attribute intensities. Higher levels of flavonoids may explain the trends for astringency. Fe and Al were present in the highest levels in boiled brews, although at levels too low to impact on health. Graphical abstract: Image 1 Highlights: Cold brewing did not affect the characteristic aroma of fermented rooibos. Cold-brewed fermented rooibos was sweeter and less astringent. Boiling improved aroma of green rooibos and increased bitterness and astringency. Fe and Al levels, highest in boiled brews, are too low to impact on health.